IMPLEMENTASI CASH MANAGEMENT SYSTEM PADA PERUM PERUMNAS - Ayu Natalia (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Cash Management System (CMS) is a type of banking product that is intended for corporate (non-private) customers to run corporate financial management online. (non tunai). This research aims to analyze how the implementation of CMS on Perum Perumnas makes the work more efficient and accurate. The objective of the research is to analyze the implementation of the transaction process using the Cash Management System. (CMS). This research method uses qualitative descriptive research methods. The research findings conclude that the implementation of the Cash Management System (CMS) can improve accountability and transparency of financial management. Implementing a cash management system (CMS) can make financial management more efficient in terms of time, access and cost. The data collection techniques performed by researchers are observations, interviews and documentation. The results of this study found that the implementation of the cash management system (CMS) on Perum Perumnas has been in accordance with the provisions.